2017
DOI: 10.3892/mmr.2017.6593
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing analyses of oral microbial diversity in healthy people and patients with dental caries and periodontal disease

Abstract: Recurrence of oral diseases caused by antibiotics has brought about an urgent requirement to explore the oral microbial diversity in the human oral cavity. In the present study, the high-throughput sequencing method was adopted to compare the microbial diversity of healthy people and oral patients and sequence analysis was performed by UPARSE software package. The Venn results indicated that a mean of 315 operational taxonomic units (OTUs) was obtained, and 73, 64, 53, 19 and 18 common OTUs belonging to Firmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…36 The apparent difference in abundance found by studies using cultures is supported by our study using 16S sequencing. The number of OTUs from the ocular surface differs from studies of the oral mucosa in which a greater number of OTUs can be identified in the pharynx 37 , 38 and studies of the gut in which up to thousands of OTUs can be identified. 39 This finding is not unexpected, as there are approximately 100 bacterial OTUs in the gut compared to one human gene, whereas in the eye the ratio is reversed at approximately one bacterial OTU for 100 human genes.…”
Section: Discussionmentioning
confidence: 93%
“…36 The apparent difference in abundance found by studies using cultures is supported by our study using 16S sequencing. The number of OTUs from the ocular surface differs from studies of the oral mucosa in which a greater number of OTUs can be identified in the pharynx 37 , 38 and studies of the gut in which up to thousands of OTUs can be identified. 39 This finding is not unexpected, as there are approximately 100 bacterial OTUs in the gut compared to one human gene, whereas in the eye the ratio is reversed at approximately one bacterial OTU for 100 human genes.…”
Section: Discussionmentioning
confidence: 93%
“…Chen et al [ 24 ] compared the microbial diversity of healthy individuals and patients with dental caries and periodontal disease and identified Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria and Fusobacteria in healthy individuals, which is similar to the microbiota observed in the NMR trachea. Interestingly, the observed microbiota changes in the trachea of NMRs in captivity (Firmicutes 18 to 42%, Proteobacteria 67 to 47%) were similar to the changes observed in oral bacteria in periodontitis patients (Firmicutes 36 to 60%, Proteobacteria 50 to 25%).…”
Section: Discussionmentioning
confidence: 95%
“…Firmicutes was reported to be the predominant phylum of dental plaque in young adults, while primary dentition and adult groups are most easily attacked by Proteobacteria (Xu et al, 2014). Some researchers found that Firmicutes decreased and Proteobacteria augmented for children, while the conclusion is totally opposite for youth and adults (Chen et al, 2017). Therefore, the oral microbial community changes along with aging, and researchers have proposed that the oral microbiome should be better investigated based on age.…”
Section: Discussionmentioning
confidence: 99%